Implementasi Pengembangan Strategi Pemasaran Syariah di Pasar Minulyo Pacitan - Pratondo Sinung Nugroho; Malta Anantyasari (Masyarakat Ekonomi Syariah Bogor, 2025)
Trading business in Minulyo market in Pacitan City run by both parents and other traders triggers to look for alternatives to increase purchasing power and income in terms of sharia. However, the decreasing purchasing power of consumers causes the market area to be quiet. Buyers flock between 02.00 in the morning until 10.00 WIB. After 10.00, the Minulyo market begins to feel quiet, even only the sellers are seen filling the market area. In this study, the researcher used a descriptive qualitative method. The data collection technique was carried out directly in the field using observation techniques, documentation, and in-depth interviews and the data sources used were from primary and secondary data. Based on the results of the study above, the Minulyo market has several shortcomings in the form of honesty ethics, sales creativity, lack of technological knowledge, and selling prices. The researcher explained the lack of buyer interest due to dishonest actions in trading ethics and ignorance of selling according to sharia law had a major impact on running a trading business. Based on the conclusion above, traders in Minulyo market have a strong spirit and determination when worshiping in Islam, but in contrast to their worship, their selling methods mostly use conventional methods rather than sharia methods, the comparison is that traders who sell using sharia methods are 20% less than conventional methods, 80% more. From here it can be concluded that the majority of Minulyo traders use conventional methods more.